Investigation of Noble Metals Colloidal Systems Formed by Laser Synthesis at Air. (8th July 2012) - Goncharov, Victor; Kozadaev, Konstantin; Shchehrykovich, Dzmitry
Abstract : The present work is dedicated to the development of formation and diagnostics methods of water colloids of noble metals (Au, Au, Pt). As anoble nanoparticles formation method, the laser synthesis at air conditions is proposed. By the implantation of noble nanoparticles into water media, the colloidal systems of noble metals can be obtained. For the aims of investigation of noble colloid parameters, the complex diagnostics method is used. Such approach deals with direct methods (scanning electron microscopy and the characteristic radiation registration) and indirect methods (absorption spectroscopy and extinction modeling by Mie theory).